Assessing Aberrant Personality in Managerial Coaching: Measurement Issues and Prevalence Rates across Employment Sectors. Issue 6 (31st January 2013) - De Fruyt, Filip; Wille, Bart; Furnham, Adrian
Abstract The convergent and discriminant validity of two methods to assess a broad spectrum of aberrant personality tendencies was examined in a large sample of managers who were administered the NEO‐PI‐R (N = 11 862) and the Hogan Development Survey (N = 6774) in the context of a professional development assessment. Five‐Factor Model (FFM) aberrant compounds, defined as linear combinations of NEO‐PI‐R facets, converged for the antisocial, borderline, histrionic, avoidant and obsessive–compulsive tendencies with their respective Hogan Development Survey counterparts. Alternative linear FFM combinations did improve convergent results for the schizoid and obsessive–compulsive pattern. Risk for various aberrant tendencies was roughly equal across different employment sectors, with a higher prevalence of borderline, avoidant and dependent tendencies in the legal and more histrionic tendencies in the retail sector. Adopting FFM aberrant compound cut‐offs developed for coaching purposes to flag at risk individuals showed that 20% to 25% of all managers qualified for at least one and 10% to 15% were flagged as at risk for two or more aberrant tendencies. The theoretical implications and the repercussions of this research for the design of professional development and coaching trajectories are discussed. Copyright © 2013 John Wiley & Sons, Ltd.